Natural deep eutectic Solvents (NADES) in sample preparation of phosphate rock and mineral supplement for elementary determination by plasma-based techniques - Santana, Ana P.R. [UNESP]; Andrade, Daniel F.; Guimarães, Taciana G.S. [UNESP]; Amaral, Clarice D.B.; Oliveirac, Andrea [UNESP]; Nogueira, Ana R.A.; Gonzaleza, Mario H. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2021)
Natural deep eutectic solvents (NADES) based on xylitol, citric acid, and malic acid were synthesized and used in ultrasound-assisted extraction (UAE) and heating-bath extraction of phosphate rock and mineral supplement samples. Arsenic, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, P and Zn were determined by inductively coupled plasma mass spectrometry (ICP-MS) and inductively coupled plasma optical emission spectrometry (ICP OES). The results showed the NADES as promising solvents for extraction of inorganic matrices compared to reference values and concentrations obtained using microwave-assisted acid digestion (MW-AD). Significant differences were observed for some elements, suggesting different chemical interactions between the synthesized NADES and each monitored element. For analytes extraction of phosphate rock, UAE presented the best results for As, Cr and P. Zinc was extracted with UAE and heating bath. Concerning mineral supplement, no significant differences were observed for Ca (UAE), Cd (UAE and heating bath), K (UAE and heating bath), Mn (UAE and heating bath), Na (UAE and heating bath), and P (UAE and heating bath). The NADES is a greener and a potentially alternative for the sample preparation compared to the official methods of analysis, can being used as selective extractor solvent in conventional sample preparation methods.
Solventes eutÉticos naturais profundos (nades) no preparo de amostras de rocha fosfÁtica e suplemento mineral para determinaÇÃo elementar por tÉcnicas de plasma
Keywords: Green chemistry; Inorganic composition; Inorganic samples; NADES; Sample preparation